Surface modified montmorillonite with cationic surfactants: Preparation, characterization, and dye adsorption from aqueous solution. Issue 4 (August 2019) - Mahmoodi, Niyaz Mohammad; Taghizadeh, Ali; Taghizadeh, Mohsen; Azimi, Mohammad
Graphical abstract: Highlights: Cetylpyridinium chloride monohydrate (CPCM) and alkyl dimethyl benzyl ammonium chloride (ADBAC) were used to modify the clay surface. Reactive red 120 was removed by the surfactant-modified montmorillonite (Mt). Critical micelle concentration point of ADBAC and CPCM were achieve 0.41 and 2.02 g/L. Surfactant adsorption obeyed the Langmuir isotherm (CPCM: 183.0 and ADBAC: 311.8 mg/g). Dye removal followed the Langmuir isotherm for the ADBAC and CPCM-modified Mt (227.3 and 243.09 mg/g). Abstract: This research tried to perform a comprehensive evaluation of dye (Reactive Red 120 (RR120)) removal by the surfactant-modified montmorillonite (Mt). For this purpose, the experiments were carried on at two levels. In the first level, the adsorption behavior of cetylpyridinium chloride monohydrate (CPCM) and alkyl dimethyl benzyl ammonium chloride (ADBAC) onto Mt was assessed by electrical conductivity technique. In this manner, the critical micelle concentration (CMC) point of ADBAC and CPCM were achieved 0.41 g/L and 2.02 g/L, respectively. Next, modified Mt, as efficient adsorbent, was utilized to toxic anionic dye adsorption from model wastewater. The attraction force between the positive surface charge of modified Mt and the negative charge of RR120 dye molecules leads to the high adsorption capacity. The mostly-known adsorption isotherm models were applied to the experimental data. The obtained data of surfactants adsorption onto Mt, as well as the adsorption data related to RR120 dye removal using modified Mt, were well fitted with the Langmuir isotherm model. The maximum Langmuir capacity for CPCM and ADBAC adsorption by Mt was achieved 183.0 mg/g and 311.8 mg/g, respectively. This amount was found 227.3 mg/g and 243.09 mg/g regarding RR120 adsorption by ADBAC and CPCM-modified Mt, respectively. Also, the hydration inhibitive ability of surfactants was investigated, and the characteristic of them was examined through extensive inhibition evaluation experiments, including settlement, zeta potential, XRD, FTIR, particle size, and SEM analyses.